2007
DOI: 10.1111/j.1462-2920.2007.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

d‐Alanyl ester depletion of teichoic acids in Lactobacillus reuteri 100‐23 results in impaired colonization of the mouse gastrointestinal tract

Abstract: The dlt operon of Gram-positive bacteria encodes proteins required for the incorporation of D-alanine esters into cell wall-associated teichoic acids (TA). D-alanylation of TA has been shown to be important for acid tolerance, resistance to antimicrobial peptides, adhesion, biofilm formation, and virulence of a variety of pathogenic organisms. The aim of this study was to determine the importance of D-alanylation for colonization of the gastrointestinal tract by Lactobacillus reuteri 100-23. Insertional inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 39 publications
4
106
2
1
Order By: Relevance
“…A mature cell wall, particularly proper biosynthesis and branching of the lipoteichoic acid, is a crucial element during L. casei establishment in the gut. This result is consistent with another contribution (32), which showed that a Lactobacillus reuteri dltA mutant was not competitive when newly introduced in the gastrointestinal tract of previously Lactobacillus-free mice. Our screening also reports the importance of one penicillin-binding protein (PBP): LSEI_0221, a D-alanyl-Dalanine carboxypeptidase that removes the last amino acid of the peptide bridge allowing the transpeptidation between two strands of peptidoglycan, is essential for gut establishment.…”
Section: Significancesupporting
confidence: 92%
See 1 more Smart Citation
“…A mature cell wall, particularly proper biosynthesis and branching of the lipoteichoic acid, is a crucial element during L. casei establishment in the gut. This result is consistent with another contribution (32), which showed that a Lactobacillus reuteri dltA mutant was not competitive when newly introduced in the gastrointestinal tract of previously Lactobacillus-free mice. Our screening also reports the importance of one penicillin-binding protein (PBP): LSEI_0221, a D-alanyl-Dalanine carboxypeptidase that removes the last amino acid of the peptide bridge allowing the transpeptidation between two strands of peptidoglycan, is essential for gut establishment.…”
Section: Significancesupporting
confidence: 92%
“…Alteration of the cell wall structure may decrease the bacteria's sensing of its environment and resistance to the environment's harsh components (49). The consequences may encompass an increase in cellular permeability to environmental compounds and to protons (50), a decrease in resistance to autolysis (32), and a modification of surface properties and hence an enhanced susceptibility to bacteriocins and antimicrobial peptides. Also, some ABC transporters can be involved in resistance to antimicrobial or peptides by excluding these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, pigs and chickens, L. reuteri is one of the dominant species in the GIT (Leser et al, 2002;Salzman et al, 2002;Brooks et al, 2003;Abbas Hilmi et al, 2007). In these animals, L. reuteri colonizes the surfaces of the stratified squamous epithelial lining of the proximal regions of the digestive tract (Tannock, 1992;Walter et al, 2007). The ecology of L. reuteri in the human gut is less clear and the organism is only detected in some subjects (Walter, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Kod soja Lb. reuteri 100-23 LTA omogućava kolonizaciju mišijeg GIT-a (Walter et al, 2007). Pokazano je da i egzopolisaharidi (EPS) koje produkuju bakterije imaju funkciju adhezije za ECM komponente.…”
Section: Faktori Adhezije Laktobacila Za Git čOvekaunclassified